2022
DOI: 10.3389/fpsyt.2022.897759
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Novel Retina−Based Diagnostic Score for Early Detection of Major Depressive Disorder: An Interdisciplinary View

Abstract: BackgroundClinically effective markers for the diagnosis of major depressive disorder (MDD) are lacking. Alterations in retinal features are closely related to the pathophysiological progression of MDD. However, the reliable retina-related diagnostic model for MDD remains to be developed. Thus, our study aimed to quantitatively evaluate retinal vascular and structural changes in MDD patients and to develop a reliable diagnostic model of MDD based on retinal parameters.MethodsSeventy-eight patients with MDD and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 48 publications
(39 reference statements)
0
9
0
Order By: Relevance
“…Previous studies have also revealed retinal changes in various psychiatric disorders, 8,9 but the specificity of these findings for BPD remains unclear. Therefore, while our study is scientifically significant, its clinical application is yet to be determined.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous studies have also revealed retinal changes in various psychiatric disorders, 8,9 but the specificity of these findings for BPD remains unclear. Therefore, while our study is scientifically significant, its clinical application is yet to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…In comparison to previous studies, our research on BPD shows distinct findings. While major depressive disorder was associated with lower retinal vessel density, thinner retinal superficial macular layers, and poorer visual function, 9 and schizophrenia and bipolar disorder were linked to significantly lower vessel density and macular thickness in the deep capillary complex, 8 TA B L E 2 Superficial retinal capillary plexus (SRCP) vessel densities in the BPD patients and healthy controls (HC) eyes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations